Tinjauan Yuridis terhadap Pelarian Pelaku Tilang dalam Perspektif Peraturan Lalu Lintas - Ayu Apriliani; Ilham Refima; Zakiyah Novitasary; Riyan Febrianto (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
Law enforcement requires every member of society to comply with applicable norms and regulations as guidelines for conduct. In Indonesia, the high rate of traffic violations and accidents is influenced by low public awareness of the law. Drivers who flee when they are about to be ticketed are generally driven by fear or because they do not meet administrative and technical vehicle requirements, such as not having complete documents, not wearing a standard helmet, having a vehicle that is not roadworthy, or being involved in other criminal acts. Such actions are punishable under Article 216 of the Criminal Code. Therefore, the police need to increase public awareness about driving safety and compliance by involving various elements of society, as well as enforcing the law firmly, consistently, and without discrimination in order to achieve traffic order and safety.